Antecedents And Outcomes On Safety Behaviour Evidence From Malaysian Logistic Sector - Yong Hvi Nee, Av (2015)
This study seeks to determine the significant antecedents of attitude, subjective norm and perceived behaviour control toward safety behaviours as well as to explain how the theory of decomposed theory of planned behavior (DTPB) is being in Malaysian Logistics. The major theoretical contribution of this study will be to consider new determinants of subjective norms and perceived behavioural controls. The study was analysed using Statistical Package for Social Science (SPSS) 17.0 and Smm1PLS 3.0 software. The model was tested using data collected from one hundred and three valid respondents. Both measurement and structural models exhibit good model fit to data. The paths estimations show that among five hypotheses tested, two are fully supported and three partially supported. The results show that moral obligation is signi ficant and positive antecedents of personal commitment to safety (PS) and safety intemalisation (SI), and government support (GS) is significant and positive antecedents of SI. PS and SI are significantly and positively related to safety performance (SP) and free from fatigue and somatic complaints (FT), while PS is significantly and positively related to job satisfaction (JS). Another finding is that influences of mass media and client partnerships are insignificant. It can be concluded that DTPB is found to be a suitable underlying theory to explain safety behaviour